2021
DOI: 10.1038/s41598-020-80047-0
|View full text |Cite
|
Sign up to set email alerts
|

A method to alleviate false-positive results of the Elecsys HIV combi PT assay

Abstract: To explore the effects of urea dissociation on reducing false-positive results of  the Elecsys HIV combi PT assay. A retrospective analysis was used to evaluate the false-positive rate of the Elecsys HIV combi PT assay. Six false-positive sera, six positive sera and six sera from patients with early HIV infection were collected. Dissociation was performed using 1 mol/L, 2 mol/L, 4 mol/L, 6 mol/L, or 8 mol/L urea, and HIV screening assay were then detected to select the appropriate concentration of urea dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The FPR was 43.4% (199/459), and it was high and similar to other reports studying HIV screening and low prevalence settings [ 15 , 16 ]. Some researches focused on assessing the role of the S/CO ratio in reducing the frequency of false-positive results [ [17] , [18] , [19] ]. We found the optimal S/CO positive threshold was 8.82 in our population which provided a sensitivity of 100% and a PPV of 90.91%.…”
Section: Discussionmentioning
confidence: 99%
“…The FPR was 43.4% (199/459), and it was high and similar to other reports studying HIV screening and low prevalence settings [ 15 , 16 ]. Some researches focused on assessing the role of the S/CO ratio in reducing the frequency of false-positive results [ [17] , [18] , [19] ]. We found the optimal S/CO positive threshold was 8.82 in our population which provided a sensitivity of 100% and a PPV of 90.91%.…”
Section: Discussionmentioning
confidence: 99%
“…1 (panel B) shows a flow diagram of the HIV testing in the retrospective study. Similar to syphilis antibodies, multiple studies have shown an association of the S/CO value of HIV screening tests with subsequent verification of HIV diagnosis using confirmatory testing and clinical information [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . Confirmation testing commonly used in the United States and some other countries includes antibody differentiation assays (in the present study was the Bio-Rad Geenius assay) and HIV RNA PCR.…”
Section: Data Descriptionmentioning
confidence: 99%